Suicidal ideation among active and nonactive/former Latter‐day Saint sexual minorities. Issue 1 (22nd May 2021) - Lefevor, G. Tyler; McGraw, James S.; Skidmore, Samuel J.
Abstract: Sexual minorities (SMs) in the Church of Jesus Christ of Latter‐day Saints (LDS) experience a number of unique risks related to their religious/spiritual and SM experience that may increase their likelihood of experiencing suicidal ideation (SI) and ultimately dying by suicide. However, it is unclear which aspects of these experiences are responsible for elevated SI. It is further unclear whether religiousness/spirituality and minority stress relate to SI similarly for active and nonactive/former LDS SMs. To address this gap, we examined data from 602 active and nonactive/former LDS SMs. Active and nonactive LDS SMs reported similar degrees of SI and minority stress but differing degrees of religiousness/spirituality with active LDS SMs reporting more religiousness/spirituality than nonactive/former LDS SMs. Several variables were associated with increased SI in both groups including positive religious coping, interpersonal religious struggles, internalized homonegativity, and concealment. Other variables were associated with decreased SI in both groups including resolving conflict between sexual and religious identities, family support, and friend support. Our results suggest that whether LDS SMs are active in their faith is an important factor to consider when understanding how religiousness/spirituality and minority stress relate to SI.